2009
DOI: 10.2174/157339909789804341
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Prevention of Type 2 Diabetes: From Research to Clinical Practice; A Systematic Review

Abstract: The prevalence of type 2 diabetes, a disease difficult to treat and expensive to manage, is increasing rapidly worldwide. It is also known that lifestyle, and particularly dietary habits, play an important role in the development of diabetes. Adherence to a healthy dietary pattern, like the Mediterranean diet, exerts a beneficial role regarding the development of diabetes. Additionally certain individual food groups and components of the diet, such as monounsaturated fatty acids, fruits, vegetables, whole grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 76 publications
4
60
0
2
Order By: Relevance
“…17,28,29 Diets that are low in red and processed meat but high in monounsaturated fatty acids, fruits, vegetables, wholegrain cereals, and dietary fiber may protect against type 2 diabetes, possibly through improving insulin sensitivity. 30,31 Low-carbohydrate diets (which often include a greater consumption of red meats and fat) have also been associated with weight loss and improvements in insulin sensitivity and glycemic control. However, to the best of our knowledge, randomized controlled trial evidence of dietary interventions and diabetes prevention exists only for low-fat, lowcalorie, plus/minus high-fiber diets.…”
Section: Dietmentioning
confidence: 99%
“…17,28,29 Diets that are low in red and processed meat but high in monounsaturated fatty acids, fruits, vegetables, wholegrain cereals, and dietary fiber may protect against type 2 diabetes, possibly through improving insulin sensitivity. 30,31 Low-carbohydrate diets (which often include a greater consumption of red meats and fat) have also been associated with weight loss and improvements in insulin sensitivity and glycemic control. However, to the best of our knowledge, randomized controlled trial evidence of dietary interventions and diabetes prevention exists only for low-fat, lowcalorie, plus/minus high-fiber diets.…”
Section: Dietmentioning
confidence: 99%
“…Observational studies have also shown that diets rich in vegetables and low in red meat and whole-fat dairy products are associated with a decreased risk of diabetes and heart attacks, whereas dietary patterns rich in red meats, processed foods, refined grains, and sweets which are rich in bread, biscuits, pizza, candies and syrups, increase risk of diabetes and CVDs [1][2][3][4][5][6][7]21,22] . In a cohort study, 512,891 adults, aged 30-79 years, were recruited from China [22] .…”
Section: Functional Food Security and The Heartmentioning
confidence: 99%
“…The traditional Mediterranean-style diet, characterized by high consumption of functional foods (vegetables, Figure 3 Changes in the nutrient content of evolutionary diet and emergence of chronic diseases. legumes, whole grains, fruits, nuts, and olive oil), moderate consumption of fish and wine, and low consumption of red and processed meat and whole-fat dairy products, is widely recognized as a healthy dietary pattern, rich in functional foods, which is similar to Paleolithic diet ( Figure 3) [1,17,[18][19][20][21][22][23][24] . Further cohort studies from Southern Europe also suggested a lower incidence of CVDs and diabetes with increasing adherence to the Mediterranean-style diet in previously healthy individuals [23] or myocardial infarction survivors [24] .…”
Section: Functional Food Security and The Heartmentioning
confidence: 99%
“…Diet is considered a milestone in diabetes primary prevention, with various dietary patterns being effective in preventing diabetes development [2][3][4]. Medical nutrition therapy (MNT) after diabetes diagnosis is of major importance.…”
Section: The Role Of Medical Nutrition Therapy In Diabetes Managementmentioning
confidence: 99%